Halogenated flame retardants and organophosphate esters in the air of electronic waste recycling facilities: Evidence of high concentrations and multiple exposures. (July 2019) - Gravel, Sabrina; Lavoué, Jérôme; Bakhiyi, Bouchra; Diamond, Miriam L.; Jantunen, Liisa M.; Lavoie, Jacques; Roberge, Brigitte; Verner, Marc-André; Zayed, Joseph; Labrèche, France
Abstract: Background: In response to a worldwide increase in production of electronic waste, the e-recycling industry is rapidly rowing. E-recycling workers are exposed to many potentially toxic contaminants, among which flame retardants (FRs), mainly suspected of being endocrine disruptors, are thought to be the most prevalent. Objective: To conduct an exposure assessment of four chemical groups of FRs in Canadian e-recycling facilities, and to identify the main cofactors of exposure. Methods: Personal air samples were collected over a workday for 85 workers in six e-recycling facilities, grouped into three facility sizes, and for 15 workers in control commercial waste facilities. Total particulate matter was measured by gravimetry with stationary air samples. FRs were collected on OSHA versatile samplers, which allow particulate and vapor phases collection. Fifteen polybrominated diphenyl ether congeners (PBDEs), nine novel brominated (NBFRs), two chlorinated (ClFRs), and fourteen organophosphate ester (OPEs) flame retardants were analysed by gas chromatography–mass spectrometry. Sociodemographic data, tasks performed and materials processed by participating workers were recorded. Tobit regressions were used to identify cofactors of exposure, and their conclusions were corroborated using semi-parametric reverse Cox regressions. Results: Thirty-nine of the 40 FRs analysed were detected in at least one air sample in e-recycling, and workers in this industry were exposed on average to 26 (range 12 to 39) different substances. The most detected chemical group of FRs in e-recycling was PBDEs with geometric mean sums of all congeners ranging from 120 to 5100 ng/m 3, followed by OPEs with 740 to 1000 ng/m 3, NBFRs with 7.6 to 100 ng/m 3, and finally ClFRs with 3.9 to 32 mg/m 3 . The most important cofactor of exposure was the size of the e-recycling facility, with the largest one presenting on average 12 times the concentrations found in the control facility. Among tasks as potential cofactors of exposure, manual dismantling and baler operation exposed workers to some of the highest concentrations of PBDEs and ClFRs. There was a reduction of up to 27% in exposure to FRs associated with a 3-year increase in seniority. Finally, particulate matter concentrations in e-recycling facilities were highly correlated with all chemical classes except OPEs, and were higher in the large facility. Conclusions: Among the FRs analysed, PBDE exposure was particularly high in e-recycling. Dust and particulate matter reduction strategies in these workplaces, together with training on proper working practices would certainly be important first steps to lower occupational exposures and prevent potential health effects. Highlights: 39 flame retardants (FRs) were detected in the air of e-recycling facilities. The most detected FR chemical class is polybrominated diphenyl ethers (PBDEs). BDE209 predominates among all FRs, especially in high-volume e-recycling facilities. Higher exposures are found with dismantling and crushing/bailing tasks. Cathode ray tubes and computer/TV screens are linked to high exposures of all FRs.